Pregnancy and delivery rates after vitrification of in vitro-produced Nelore (Bos indicus) embryos under field conditions - Pereira, Lucas C.; Ferreira-Silva, José C.; Cantanhêde, Ludymila C.; Basto, Sarah R. L.; Veloso Neto, Humberto F.; Moura, Marcelo T.; Oliveira, Marcos Antonio L. (Revista Colombiana de Ciencias Pecuarias, 2019)
Background: Cryopreservation preserves cellular viability under low temperatures, resulting in diminished intracellular enzymatic activity and reduced cellular metabolism that ultimately allows preserving genetic material for indefinite periods of time. Embryos submitted to cryopreservation suffer from considerable morphological and functional damage, resulting in reduced survival and development rates. Objective: To evaluate pregnancy and delivery rates of in vitro-produced (IVP) Nellore (Bos indicus) embryos after vitrification under field conditions. Methods: The IVP embryos at blastocyst (Bl) and expanded blastocyst (Bx) were transferred fresh (n= 137) or after vitrification (n= 127). Results: Pregnancy rates at 35 d for fresh embryos were lower in Bl (41.6) than in Bx (60.9) (p0.05). Pregnancy loss at 60 d were similar (p>0.05) for both fresh (Bl: 3.1 and Bx: 4.8) and vitrified embryos (Bl: 1.9 and Bx: 4.7). Delivery rates were similar between groups (p>0.05). Conclusion: Both pregnancy and delivery rates of Bos indicus IVP embryos vitrified under field conditions are indistinguishable from fresh embryos.